Sex similarities versus gender symmetry - YONG, Jose C. (Institutional Knowledge at Singapore Management University, 2016)
Men and women have similar and different mate preferences, which include preferences for type of relationship duration as well as the types of traits that are sought out within each mating duration. This entry covers some of the key similarities and differences in preferences for both mating context and partner traits within context.